Validitas Lembar Aktivitas Peserta Didik (LAPD) dengan Pendekatan Contextual Teaching and Learning untuk Meningkatkan Keterampilan Proses Sains Peserta Didik pada Materi Hidrolisis Garam Fase F - Wahyuni Wulandari; Rusmini Rusmini (Faculty of Mathematics and Natural Sciences, Universitas Negeri Surabaya, 2026)
This study aims to develop and validate Student Activity Sheets (LAPD) using a contextual teaching and learning approach to improve students' science process skills on the topic of salt hydrolysis. This type of research uses Research and Development (R&D) with the 4D development model (Define, Design, Develop, and Disseminate), which is limited to the Develop stage. The Define stage includes front-end analysis, student analysis, task analysis, and concept analysis. The Design stage includes media selection, format selection, initial design, and preparation of science process skills tests. The Develop stage involves assessing the LAPD based on content validity and construct validity using a Likert scale (1-5), conducted by two chemistry lecturers and one chemistry teacher. The LAPD is considered valid if it receives a mode score from all validators with the criteria of